(untitled) (Revista de Ciências Agroveterinárias, 2020)
The growth of 81 indigenous Arbia goat kids reared in an intensive system in Setif in northeastern Algeria was observed between birth and 70 days of age. The kids were dam-raised during the first month and then provided with 150 g/head/day of a total mixed ration and oat hay. The kids’ live weights were assessed at fasting and at different ages: 0, 10, 21, 30, 42, 60, and 70 days. The average daily gains (ADG) were also calculated. Growth results were presented for all kids by sex and litter size. The average birth weight was W0 = 2.53±0.19 kg, while the average weight at 70 days was W70 = 10.1±1.54 kg, which correspond to an overall daily weight gain of ADG0-70 = 108±21 g/day. The study showed that birth weight was affected by litter size, while growth after birth was mainly affected by sex. Birth weights were similar between males and females, but males grew faster (p<0.001) after birth. Single kids were heavier (p<0.05) than twins at 70 days of age, which is the consequence of a heavier birth weight and a faster growth rate in the first 10 days after birth (ADG0-10). After 10 days, litter size did not affect ADG. Compared to other indigenous populations, Arbia goat kids demonstrated valuable growth potential for meat production.